Pengaruh model discovery learning terintegrasi pembelajaran berdiferensiasi terhadap kemampuan menganalisis peserta didik - Ingati, Embun Seger; Widianto Atmojo, Idam Ragil (Universitas Sebelas Maret, 2026)
This study aims to determine the influence of the Discovery Learning model integrated with differentiated instruction on the analytical skills of fifth-grade students in the Natural and Social Sciences (IPAS) subject at SD Negeri 2 Wonosobo. The background highlights the importance of 21st-century skills, particularly analytical skills essential for facing globalization challenges. Initial observations indicated varied and suboptimal analytical abilities among students. The research employed a quasi-experimental method using a Nonequivalent Control Group Design, involving two classes: the experimental group taught with the Discovery Learning model integrated with differentiated instruction and the control group utilizing the Problem Based Learning (PBL) model. Data were collected through pretest and posttest assessments of analytical skills. Results indicate a significant improvement in analytical skills in the experimental group, with an average posttest score of 85.81 compared to 77.21 in the control group. The highest influence was observed among auditory learners, followed by kinesthetic and visual learners. These findings affirm the effectiveness of the Discovery Learning model integrated with differentiated instruction in enhancing students' analytical skills. Recommendations are provided for implementing this model in elementary school education.